2018
DOI: 10.1016/j.ihj.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aortic aneurysms in trans-catheter aortic valve replacement: A single center experience

Abstract: BackgroundPatients who undergo trans-catheter aortic valve replacement (TAVR) may have concomitant aortic aneurysms. We sought to clarify the incidence of aortic aneurysms and its impact on clinical outcomes among patients undergoing TAVR.MethodsWe performed a retrospective analysis of patients with severe symptomatic aortic stenosis who underwent TAVR from January 2012 to June 2016. Multi-detector computer tomography (MDCT) was performed on all patients and images were reviewed to identify thoracic and abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Accordingly, did the types of TAVI bioprostheses (balloon-expanding, self-expanding, and mechanically expanding) differ significantly between patients with and without an aortic aneurysm in the present study 3 ? Importantly, particular performance of TAVI specifically by more experienced operators along with the cautious use of more resilient and smaller delivery systems in patients with an aortic aneurysm might have neutralized the potential difference between the groups particularly in terms of periprocedural vascular complications 3 …”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Accordingly, did the types of TAVI bioprostheses (balloon-expanding, self-expanding, and mechanically expanding) differ significantly between patients with and without an aortic aneurysm in the present study 3 ? Importantly, particular performance of TAVI specifically by more experienced operators along with the cautious use of more resilient and smaller delivery systems in patients with an aortic aneurysm might have neutralized the potential difference between the groups particularly in terms of periprocedural vascular complications 3 …”
mentioning
confidence: 75%
“…Second, as opposed to the conventional belief, the diameter of a given aneurysm might not serve as the sole determinant of its complication risk (rupture, dissection, and so forth), suggesting the particular roles of certain structural factors including the presence of mural thrombus, degrees of local inflammation, and calcification within the aneurysmatic wall 6 as well as the magnitude of wall thickness. Therefore, relatively small aneurysm sizes, and probably, favorable structural features (diminishing vulnerability of aneurysmal sacs) might have precluded excess iatrogenic or long-term spontaneous complications associated with aneurysms in the present study 3 . Importantly, structural characteristics of aneurysmal sacs (on top of aneurysm diameter) should particularly be evaluated through advanced diagnostic modalities such as magnetic resonance imaging, positron emission tomography, and so forth 6 for the prediction of procedural and long-term complication risks (and hence, to implement the most proper therapeutic strategy) in the setting of TAVI.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Interestingly, case reports have demonstrated successful transapical TAVR in combination with thoracic endovascular aortic repair in a patient with 8.0 cm ascending aneurysm and 4.2 cm aortic arch aneurym as a possible approach in high-risk inoperable patients. Furthermore, it has been reported that there was no increase of the ascending aortic aneurym after TAVR in BAV anatomy [22].…”
Section: Transcatheter Aortic Valve Replacement (Tavr)mentioning
confidence: 97%